Hubungan Antropometri dengan Sindrom Metabolik pada Pekerja Kantor di Universitas Trisakti: Studi Potong Lintang - Trilaksmi, Antin; Nazma, Diani; Soesilo, Christian; Sari, Meiriani; Mahardieni, Karlina; Panduwati, Lira (Jurnal Biomedika dan Kesehatan, 2025)
Background Metabolic syndrome is a disease with an increasing prevalence and a high health burden. Most individuals with metabolic syndrome have a sedentary lifestyle, such as office workers who rarely undergo health check-ups. Therefore, this study aims to investigate the profile and correlation of anthropometric indices and metabolic syndrome parameters among office workers at Trisakti University. Methods Office workers from the Faculty of Medicine, Trisakti University, were recruited for this study, and informed consent was obtained. Subsequently, data on blood pressure, laboratory tests including glucose levels and lipid profiles, as well as anthropometric measurements such as weight, height, body mass index (BMI), waist circumference, and hip circumference were collected. The data were statistically analyzed using univariate analysis and bivariate correlation analysis with Spearman's test, as well as intergroup difference tests using the Kruskal-Wallis test and ANOVA. Results The average age of the subjects was 41.46±9.87 years. The data showed that approximately 43.33% had hypertension, with a concentration of data in the profiles of grade I obesity, normotension, normal triglyceride levels, normal blood glucose levels, and normal high-density lipoprotein (HDL) levels. The analysis revealed a significant difference in HDL levels between the normal BMI group and the overweight BMI group (MD: 9.534; 95% CI: 1.68-17.39; p = 0.018). A very weak and non-significant correlation was found between BMI and metabolic syndrome parameters. Conclusions Anthropometric indices reflect central obesity as well as the characteristics of metabolic syndrome among employees at the Faculty of Medicine, Trisakti University.